2014
DOI: 10.1007/s11060-014-1410-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity of glioma cells to 5-fluorocytosine following photo-chemical internalization enhanced nonviral transfection of the cytosine deaminase suicide gene

Abstract: Despite advances in surgery, chemotherapy and radiotherapy, the outcomes of patients with GBM have not significantly improved. Tumor recurrence in the resection margins occurs in more than 80 % of cases indicating aggressive treatment modalities, such as gene therapy are warranted. We have examined photochemical internalization (PCI) as a method for the non-viral transfection of the cytosine deaminase (CD) suicide gene into glioma cells. The CD gene encodes an enzyme that can convert the nontoxic antifungal ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A modified form of PDT, photochemical internalization (PCI) has been shown to greatly enhance gene insertion efficiency for both viral as well as nonviral gene transfection protocols [16, 32, 33]. Due to the rapid attenuation of light in tissue this enhanced transfection efficiency would be limited to the illuminated targeted tumor site, thus avoiding transfection of off target normal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified form of PDT, photochemical internalization (PCI) has been shown to greatly enhance gene insertion efficiency for both viral as well as nonviral gene transfection protocols [16, 32, 33]. Due to the rapid attenuation of light in tissue this enhanced transfection efficiency would be limited to the illuminated targeted tumor site, thus avoiding transfection of off target normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of a stable F98 cd cell line, expressing both the cytosine deaminase (CD) and uracil phosphoribosyl transferase (UPRT) genes has been described in detail previously [16]. Briefly, F98 cells were initially transfected with a plasmid consisting of the fusion plasmid pSELECT-zeo-Fcy::fur, (InvivoGen, San Diego, California) and the jetPEI carrier (Polyplus-transfection, Strasbourg France) following the manufacture’s protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, yCD can be fused with E. coli uracil phosphoribosyl transferase (UPRT) which is absent in mammalian cells. UPRT can directly convert 5-FU to 5-FdUMP (Wang et al 2014) resulting in significant improvement of activity and enhanced cancer cell killing efficiency in prostate, ovarian, colon, and breast cancers (Miyagi et al 2003; Richard et al 2006). Some studies have also shown that yCD:UPRT/5-FC system may not get affected by acquired 5-FU resistance and could potentially kill both proliferating and non-proliferating cancer cells (Richard et al 2006; Leveille et al 2011).…”
Section: Enzyme/prodrug Systemsmentioning
confidence: 99%
“…Importantly, the bystander effect, where activated drug is exported from the transfected cells into the tumor microenvironment, plays an important role by inhibiting growth of adjacent tumor cells. We have recently published a series of studies employing photochemical internalization (PCI) enhanced gene transfection into glioma cells from human and rat [5,6]. The concept of PCI is based on using light and photosensitzers to promote endosomal escape of trapped macro-molecules, thus avoiding lysosomal degradation [7,8].…”
Section: Gene Therapy For Cancermentioning
confidence: 99%